Neuroleptic malignant syndrome and subsequent clozapine-withdrawal effects in a patient with refractory schizophrenia - Cheng M; Gu H; Zheng L; wang H; Zhong Z; Wen S (Neuropsychiatric Disease and Treatment, 2016)
Minfeng Cheng,* Huaying Gu,* Liangrong Zheng, Houliang Wang, Zhiyong Zhong, Shenglin Wen Department of Psychiatry, Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Here, we report a female patient developing neuroleptic malignant syndrome following the use of a combination of clozapine and haloperidol. Subsequently, the patient presented withdrawal effects after an abrupt discontinuation of clozapine. Psychiatrists not aware of possible clozapine-withdrawal effects may misdiagnose as a part of the primary mental illness or as the initial symptoms worsening, if unrecognized. Keywords: clozapine, neuroleptic malignant syndrome, withdrawal effect, schizophrenia